A Consistent Model for the Key Complex in Chronic Beryllium Disease - Mera-Adasme, R (De Gruyter Open Ltd, 2020)
A hypothesis on the structure of the key complex in chronic beryllium disease (CBD) is discussed with respect to the current knowledge on CBD, and with respect to the constraints implied by the coordination chemistry of beryllium and experimental data on the engaged protein complexes. The structure hypothesis is based on the [Be4O]6+ moiety as a coordination center, which is also found in the so called "basic beryllium carboxylates". The structure of a small molecular model, optimized at the DFT level of theory, is used to compare the structural demands of this coordination center with a structure of the in vitro model of a beryllium immunoprotein complex determined previously by protein crystallography (Clayton & al., Cell 2014, 158, 132). 9Be NMR chemical shielding values, quadrupole coupling constants and asymmetry parameters (η) have been calculated. © 2020 Walter de Gruyter GmbH, Berlin/Boston 2020.
Keywords: beryllium disease; protein structure 4p4k; toxicity of beryllium